Mexican-American entrepreneurship - Robert W. Fairlie; Christopher Woodruff (Institute for the Study of Labor (IZA), 2008)
Although business ownership has implications for income inequality, wealth accumulation and job creation, surprisingly little research explores why Mexican-Americans are less likely to start businesses and why the businesses that they start are less successful on average than non-Latino whites. We conduct a comprehensive analysis of Mexican-American entrepreneurship using microdata from the 2000 U.S. Census, the matched and unmatched March and Outgoing Rotation Group Files of the Current Population Survey from 1994 to 2004, and the Legalized Population Survey (LPS). We find that low levels of education and wealth explain the entire gap between Mexican immigrants and non-Latino whites in business formation rates. Nearly the entire gap in business income for Mexican immigrants is explained by low levels of education and limited English language ability. Using the natural experiment created by the Immigration Reform and Control Act (IRCA), we find that legal status represents an additional barrier for Mexican immigrants. A conservative estimate suggests that the lack of legal status reduces business ownership rates by roughly seven-tenths of a percentage point for both men and women. Human and financial capital deficiencies are found to limit business ownership and business success among second and third-generation Mexican-Americans, but to a lesser extent. These findings have implications for the debates over the selection of immigrants and the assimilation of Mexican-Americans in the U.S. economy.
urn:nbn:de:101:1-2008052786
Keywords: J15; 330; Mexican-Americans; entrepreneurship; inequality; Unternehmer; Unternehmensgründung; Mexikaner; USA